Isolation, identification and sensory evaluation of kokumi peptides from by‐products of enzyme‐modified butter. (15th June 2022) - Yang, Zhijie; Wang, Jiao; Han, Zhaosheng; Blank, Imre; Meng, Fanyu; Wang, Bei; Cao, Yanping; Tian, Huaixiang; Chen, Chen
Abstract: Background: Enzyme‐modified butter is used as a common raw material to obtain a natural milk flavor. Butter protein is a by‐product in butter processing that can be used as substrate to produce taste‐active peptides, which can create additional value and new application opportunities, making the method more environmentally friendly. Results: Putative kokumi peptides from hydrolysates of protein by‐products were isolated by gel filtration chromatography and reversed‐phase high‐performance liquid chromatography. The isolated peptide fraction with the most pronounced kokumi taste was screened by sensory evaluation and electronic tongue analysis. Eleven peptides were identified by matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry. Six peptides were synthesized to verify their taste characteristics. Five synthetic peptides (FTKK, CKEVVRNANE, EELNVPG, VPNSAEER and YPVEPFTER) showed different intensity levels of kokumi taste. Of these peptides, the decapeptide CKEVVRNANE had the highest kokumi intensity. Conclusion: The newly identified kokumi peptides increased the kokumi taste intensity and showed some synergistic effect with umami taste. Both termini of the peptides seem to play an important role in taste characteristic. Glu residue at both termini can increase the kokumi taste intensity. This work indicated that it was feasible to produce kokumi peptides by enzymatic hydrolysis of the protein by‐products of butter. © 2022 Society of Chemical Industry.